Beauty versus ugliness - Omer, Spahic (IIUM Today, 2019)
Prophet Muhammad (peace and blessings be upon him) established the doctrines that Allah is beautiful and loves beauty (Sahih Muslim, Hadith No. 131), that He is good and accepts only that which is good (Sahih Muslim, Hadith No. 1686), and that He loves to see the effects of His blessings and favors on people (Jami’ al-Tirmidhi, Hadith No. 2963). This implies that since Almighty Allah loves beauty, He created everything perfect and beautiful. Moreover, He also wants His servants to do so, that is, to love beauty, be beautiful and generate beauty through words, deeds, character, garments, general outward appearance, and the cultural and civilizational creations of theirs. In doing so, however, people must subscribe to and apply only the highest heavenly standards of goodness and beauty, without contaminating them with the effects of their intrinsic inadequacies, myopia and whims. It is on account of this that Islam abhors ugliness with all its physical and metaphysical dimensions and features. It does so, for example, as much in evil speech, disposition and conduct, as in ungodly elements of culture, art and architecture.